Integration of molecular testing to confirm the presence of Tritrichomonas foetus in cattle from northwest Mexico - Flores-Encinas , Luis-Ángel; Torres-Simenta, José-Florentino; Figueroa-López, Alejandro-Miguel; Sánchez-Castro, Miguel-Ángel; Aragón-López, Carlos-Eduardo; Morales-Pablos, Marcela-Ivone; Leyva-Corona , José-Clemente (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Bovine trichomoniasis is a venereal disease caused by Tritrichomonas foetus (T. foetus) that significantly impairs the reproductive health of cattle. While bulls are asymptomatic carriers of this protozoan, cows infected with T. foetus exhibit embryonic deaths, abortions, reproductive tract infections or infertility. In México, the first report of T. foetus was made more than 60 years ago and, despite of the importance of trichomoniasis in cattle, efforts to control it through surveillance, diagnosis and adequate characterization have been scarce. Objective: To confirm the presence of T. foetus in animals from northwest México via molecular detection, sequencing, and phylogenetic analyses. Methods: Forty biological samples (smegma and mucopurulent vaginal secretion) were collected and analyzed by PCR technique to identify T. foetus using specific primers. Utilizing samples positive for T. foetus, sequencing and phylogenetic analyses were performed over the molecular structure of the generated amplicons to verify their homology and genetic relationships. Results: The PCR technique identified T. foetus in smegma and in clinical cases of metritis. Sequences obtained from PCR products revealed a 99.65% of similarity and a bootstrap of 99% with isolates of T. foetus reported in China, Spain, and USA. Based on the sequencing results, five new Mexican isolates of T. foetus were published in NCBI. Conclusion: This is the first report confirming the presence of T. foetus in México using sequencing and phylogenetic analyses from positive cattle samples. Our research effort represents the basis for developing alternative and accurate tests to diagnose T. foetus as part of the strategy to epidemiologically control bovine trichomoniasis in the country